2022
DOI: 10.1002/adfm.202200771
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reversible Evolution of Solid Electrolyte Interface in Nonflammable Triethyl Phosphate Electrolyte Enabling Safe and Stable Potassium‐Ion Batteries

Abstract: Potassium-ion batteries (PIBs) are a favorable alternative to lithium-ion batteries (LIBs) for the large-scale electrochemical storage devices because of the high natural abundance of potassium resources. However, conventional PIB electrodes usually exhibit low actual capacities and poor cyclic stability due to the large radius of potassium ions (1.39 Å). In addition, the high reactivity of potassium metal raises serious safety concerns. These characteristics seriously inhibit the practical use of PIB electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…The sputtering XPS results for the GDC-CP and CAC-CP electrodes exhibit the electrolyte interface films are both rich in KF with the thickness of about 10 nm (Figure 2d-f). [24] The scanning electron microscope (SEM) and transmission electron microscope (TEM) present the uniform and dense electrolyte interface films with the thickness of about 3.0 nm for the GDC-CP and about 5.0 nm for the CAC-CP, respectively (Figure S38, Supporting Information). [4a, 25] The atomic force microscope (AFM) suggests that Young's modulus of the GDC and CAC electrode surfaces decreases significantly and becomes more uniform after pre-potassiation (Figure 2g-j The functions of the pre-formed electrolyte interface films on the electrodes by pre-potassiation treatment are further investigated during the discharge/charge process.…”
Section: Resultsmentioning
confidence: 99%
“…The sputtering XPS results for the GDC-CP and CAC-CP electrodes exhibit the electrolyte interface films are both rich in KF with the thickness of about 10 nm (Figure 2d-f). [24] The scanning electron microscope (SEM) and transmission electron microscope (TEM) present the uniform and dense electrolyte interface films with the thickness of about 3.0 nm for the GDC-CP and about 5.0 nm for the CAC-CP, respectively (Figure S38, Supporting Information). [4a, 25] The atomic force microscope (AFM) suggests that Young's modulus of the GDC and CAC electrode surfaces decreases significantly and becomes more uniform after pre-potassiation (Figure 2g-j The functions of the pre-formed electrolyte interface films on the electrodes by pre-potassiation treatment are further investigated during the discharge/charge process.…”
Section: Resultsmentioning
confidence: 99%
“…The sputtering XPS results for the GDC‐CP and CAC‐CP electrodes exhibit the electrolyte interface films are both rich in KF with the thickness of about 10 nm (Figure 2d–f). [24] The scanning electron microscope (SEM) and transmission electron microscope (TEM) present the uniform and dense electrolyte interface films with the thickness of about 3.0 nm for the GDC‐CP and about 5.0 nm for the CAC‐CP, respectively (Figure S38, Supporting Information) [4a, 25] . The atomic force microscope (AFM) suggests that Young's modulus of the GDC and CAC electrode surfaces decreases significantly and becomes more uniform after pre‐potassiation (Figure 2g–j and Figure S39, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[60][61][62] Furthermore, the formation of a thin and uniform SEI improves the cycling stability and rate performance of the battery. [31,[63][64][65][66] Both solvents and salts play important roles in the formation of SEI. The generation of the SEI layer proceeds through three major steps: first, the salt anions and the solvent molecules in the electrolyte are reduced.…”
Section: Organic Liquid Electrolytesmentioning
confidence: 99%
“…More recently, Chen et al explored the electrochemical performance of ZnP 2 as the anode materials in the TEP‐based electrolyte (2.0 m KFSI in TEP). [ 65 ] In addition to the inherent non‐flammable advantage of TEP‐based electrolytes, the authors found that the sulfur‐containing species formed by the decomposition of KFSI in SEI can reversibly evolve and transform through charge/discharge processes in TEP‐based electrolytes, instead of repeated formation and degradation in EC/DEC‐based electrolytes. This interesting reversible SEI helps improve the cycling stability of the electrode (Figure 7 h,i).…”
Section: Organic Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation